A cutaneous metastasis of unresectable rectal adenocarcinoma: A case report and literature review - Hakami, Riyadh (Int J Surg Case Rep, 2020)
BACKGROUND: Colorectal cancer is ranked third among the most commonly diagnosed malignancies and fourth among the leading causes of cancer death in the world. However, only a few case reports are found in the literature regarding skin metastasis originating from rectal cancer, which usually shows widespread disease and poor prognosis. Approximately, 0.8% of the patients will have skin lesion as the first indication of a silent internal malignancy, which is rare. CASE REPORT: We report a complicated case of a 45-year-old male patient who referred to our highly specialized governmental hospital for diversion loop colostomy as well as biopsies of rectal and inguinal skin areas followed by palliative radiation therapy to the pelvis. Histopathological exam of rectal biopsies revealed moderately differentiated rectal adenocarcinoma, while the skin of the right inguinal area showed metastatic cutaneous rectal adenocarcinoma. Unfortunately, palliative radiation therapy was not started as the patient passed away secondary to respiratory failure which ended by cardiopulmonary arrest. CONCLUSION: A patient who is having new or evolving skin lesions with an oncology history should be well investigated as cutaneous metastasis is a strong possibility.